First report on detection of Hepatozoon ayorgbor in Rhipicephalus haemaphysaloides and Hepatozoon colubri in Haemaphysalis sulcata and Hyalomma anatolicum: risks of spillover of Hepatozoon spp. from wildlife to domestic animals - Tila, Hadia; Khan, Mehran; Almutairi, Mashal M.; Alouffi, Abdulaziz; Ahmed, Haroon; Tanaka, Tetsuya; Tsai, Kun-Hsien; Ali, Abid (Frontiers in Veterinary Science, 2023)
This study aimed to detect Hepatozoon spp. in ticks infesting asymptomatic domestic animals and to provide insight into their potential spillover from wild to domestic animals. In total, 537 tick specimens were collected in Khyber Pakhtunkhwa, Pakistan, and morphologically identified. The extracted DNA from a subset of each tick species was subjected to PCR to amplify 18S rRNA fragments of Hepatozoon spp. By BLAST analysis, the Hepatozoon sp. detected in Hy. anatolicum infesting cows and in Ha. sulcata infesting sheep showed 99.7% maximum identity with Hepatozoon colubri. Similarly, the Hepatozoon sp. detected in R. haemaphysaloides infesting goats shared 99.49% maximum identity with Hepatozoon ayorgbor, and the Hepatozoon sp. detected in R. sanguineus infesting dogs exhibited 99.7% identity with Hepatozoon canis. Having an overall infection rate (9.3%; 16/172), the highest infection rate was recorded for each H. canis, and H. colubri (3.5%; 6/172), followed by H. ayorgbor (2.3%; 4/172).In the phylogenetic tree, H. colubri clustered with corresponding species from Iran, H. ayorgbor clustered with the same species from Croatia, Ghana, and Portugal, and H. canis clustered with the conspecifics from Iran, Israel, Romania, and Zambia. Regarding the potential spillover of Hepatozoon spp. from wildlife through ticks, free ranging animals was at higher risk compared to confined animals (RR = 3.05), animals consuming food from wildlife habitats were at higher risk compared to those consuming domestic food (RR = 3.06), and animals residing in farm buildings located in wildlife habitats were at higher risk compared to those residing in farm buildings located in villages (RR = 3.28). In addition to the first report on H. canis in R. sanguineus in Pakistan, this is the earliest data showing H. ayorgbor in R. haemaphysaloides and H. colubri in Ha. sulcata and Hy. anatolicum. These preliminary findings suggest a potential spillover of Hepatozoon spp. from wild to domestic animals via ticks under certain risk factors.